Studying the effect of exposure time for Nanocomposite Gold Nanoparticles with Hyaluronic acid synthesis using the atmospheric air jet plasma (Texas Journal of Multidisciplinary Studies, 2022)
The atmospheric air cold plasma has been used in the manufacture of gold nanomaterials. Where plasma was generated non-thermal atmospheric pressure using diameter of 1 mm. Aqueous gold tetrachloride salts HAuCl4.4H2O is used for production of gold nanoparticles with Hyaluronic Acid (HA). The experiment was conducted in parameter of time, where the use aqueous gold tetrachloride salts HAuCl4.4H2O in concentration of 1 mM with Hyaluronic Acid (HA) in concentration of 1mM in a different exposure time ( 3, 4, 5, 6 ) min. To insure the typical preparing of the nanoparticles, UV-visible and X-ray have been conducted for that purpose. Morphology of the AuNPs were carried out by FESEM. The outcome of the study revealed that the atmospheric air cold plasma is a promising technique to be used in production of the nanoparticle’s materials for the medical application